Accounting for the environment more talk and little progress - Freedman, Martin; Jaggi, Bikki (Advances in environmental accounting & management ;, 2014)
Advances in environmental accounting & management aims to enhance the understanding of global environmental issues, especially valuation and disclosure of environmental impact of firms' activities, encouraging management to improve firms' environmental performance and disclosures. The series also wants to make management, investors and other stakeholders aware of the potential financial and economic consequences of failure to address environmental issues. To achieve this, Advances in environmental accounting & management seeks to enable regulators to evaluate firms' environmental performance, increase public and managerial awareness of global concerns of environmental pollution, and encourage management to improve the environmental performance of their companies. Volume 5 of Advances in environmental accounting & management typifies these aims, addressing topics such as sustainability, environmental liabilities, social investing and global warming and accounting.